The role of variation at AβPP, PSEN1, PSEN2, and MAPT in late onset Alzheimer's disease - Gerrish, Amy; Frölich, Lutz (Journal of Alzheimer's disease, 2012)
Rare mutations in AβPP, PSEN1, and PSEN2 cause uncommon early onset forms of Alzheimer's disease (AD), and common variants in MAPT are associated with risk of other neurodegenerative disorders. We sought to establish whether common genetic variation